Compositional profiling and molecular docking studies of Eucalyptus polybrachtea essential oil against mucormycosis and aspergillosis - Arun Dev Sharma; Inderjeet Kaur; Amrita Chauhan (BioTechnologia, 2023)
Essential oil (EO) from Eucalyptus polybrachtea is used as complementary and traditional medicine worldwide. The present study aimed at compositional profiling of EO and molecular docking of EO’s bioactive compound 1,8 cineole against fungal enzymes involved in the riboflavin synthesis pathway, namely riboflavin synthase (RS), riboflavin biosynthesis protein RibD domain-containing protein (RibD), and 3,4-dihydroxy-2-butanone 4-phosphate synthase (DBPS) as apposite sites for drug designing against aspergillosis and mucormycosis, and in vitro confirmation. The compositional profile of EO was completed by GC-FID analysis. For molecular docking, the Patch-dock tool was used. The ligand-enzyme 3-D interactions were examined, and ADMET properties (absorption, distribution, metabolism, excretion, and toxicity) were calculated. GC-FID discovered the occurrence of 1,8 cineole as a major component in EO, which was subsequently used for docking analysis. The docking analysis revealed that 1,8 cineole actively bound to RS, RibD, and DBPS fungal enzymes. The results of the docking studies demonstrated that the ligand 1,8 cineole exhibited H-bond and hydrophobic interactions with RS, RibD, and DBPS fungal enzymes. 1,8 cineole obeyed Lpinsky’s rule and exhibited adequate bioactivity. Wet-lab authentication was achieved by using three fungal strains: Aspergillus niger, Aspergillus oryzae , and Mucor sp. Wet lab results indicated that EO was able to inhibit fungal growth.